2010
DOI: 10.1242/jcs.060434
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic organisation of prolactin gene expression in living pituitary tissue

Abstract: SummaryGene expression in living cells is highly dynamic, but temporal patterns of gene expression in intact tissues are largely unknown. The mammalian pituitary gland comprises several intermingled cell types, organised as interdigitated networks that interact functionally to generate co-ordinated hormone secretion. Live-cell imaging was used to quantify patterns of reporter gene expression in dispersed lactotrophic cells or intact pituitary tissue from bacterial artificial chromosome (BAC) transgenic rats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 31 publications
2
69
0
Order By: Relevance
“…4E). These patterns also differed from that of adult pituitary tissue (Harper et al, 2010). Differences could also be detected in the transcription patterns of the tissue ( …”
Section: Transcription Of Prolactin In Real-time In Late Embryonic Anmentioning
confidence: 85%
See 2 more Smart Citations
“…4E). These patterns also differed from that of adult pituitary tissue (Harper et al, 2010). Differences could also be detected in the transcription patterns of the tissue ( …”
Section: Transcription Of Prolactin In Real-time In Late Embryonic Anmentioning
confidence: 85%
“…To assess the real-time transcription activity of the PRL gene, transgenic rats were previously generated that express the luciferase reporter gene under the regulation of the human PRL locus (hPRL-Luc49), followed by bioluminescence imaging of cells or tissue in culture in a temperature-, CO -and humiditycontrolled imaging chamber (Semprini et al, 2009;Harper et al, 2010). Characterisation of the reporter transgene showed that it faithfully reflects endogenous Prl gene transcription activity as it is expressed in the correct cell type (lactotroph cells) and responds appropriately to various regulators of Prl expression (Semprini et al, 2009;Harper et al, 2010).…”
Section: Organisation Of Transcriptionally Active Lactotroph Cells Wimentioning
confidence: 99%
See 1 more Smart Citation
“…An important study has recently used transgenic rat models with fluorescent reporter and real-time confocal imaging of fluorescent pituitary tissue to analyze the spatiotemporal patterns of gene expression in relation to tissue structure (Harper et al 2010). This study showed a long-term coordination of pituitary cell behavior when the tissue structure appears whereas dispersion of cells in a primary culture provides high variability and independence of promoter activity.…”
Section: A Model For Tunability Of the Rgvg In Stressful And Fluctuatmentioning
confidence: 99%
“…The library of reporter genes available has significantly expanded over the years, and includes enzymes such as b-galactosidase, which generate a colourimetric product or chloramphenicol acetyl transferase, which catalyses the synthesis of radiolabelled (and latterly fluorescent) product, to enzymes such as luciferase that catalyses the production of light from the substrate luciferin to give a measure of gene activation (Frawley et al 1994, White et al 1995. Luciferase can be used to analyse the induction of gene expression across a population of cells by assaying the whole cell lysate, and also to dynamically analyse gene expression in a single cell through microscopy, measuring the photon output from a single cell (Harper et al 2010).…”
Section: Reporter Genesmentioning
confidence: 99%